Political Theory in 21st Century Peru: The Gamio-Hernando Debate (2001-2025) - Pérez Crespo, Carlos Eduardo (2025)
Having completed the first two decades of the current century, it seems necessary to establish an initial overview of the intellectual development of political theory in Peru. The purpose of this review is to explain and reflect on the recent debate between Gonzalo Gamio and Eduardo Hernando, two renowned political science professors, which took place at the Universidad Peruana de Ciencias Aplicadas (UPC) on April 23, 2025. This event marked the culmination of the most significant debate on political theory in Peru during the first quarter of the 21st century. First, this review will outline the intellectual and academic profiles of each of these authors. It will then analyze the central themes of their most recent debate, also taking into account their previous exchanges in 2001 and 2007. Finally, it will briefly discuss the relevance of the ideas defended by both authors for understanding Peru through the lens of political theory.